2014
DOI: 10.1155/2014/148743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CuO Nanoparticles over Isolated Bacterial Strains from Agricultural Soil

Abstract: The increased use of the nanoparticles (NPs) on several processes is notorious. In contrast the ecotoxicological effects of NPs have been scarcely studied. The main current researches are related to the oxide metallic NPs. In the present work, fifty-six bacterial strains were isolated from soil, comprising 17 different OTUs distributed into 3 classes: Bacilli (36 strains), Flavobacteria (2 strains), and Gammaproteobacteria (18 strains). Copper oxide nanoparticles (CuONPs) were synthesized using a process of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…CuO NPs were previously shown to interact with the plasma membrane of bacteria, leading to holes in the membrane and the lysis of bacterial cell. 29 The released Cu 2+ ions were also found to interact with negatively charged components of the cell wall and membrane, leading to denaturation and alteration of the membrane proteins. 30 Copper ions inside the bacterial cell generate ROS, leading to alterations in cellular signalling and interfering with the nucleic acid, resulting in an altered helical structure.…”
Section: Resultsmentioning
confidence: 99%
“…CuO NPs were previously shown to interact with the plasma membrane of bacteria, leading to holes in the membrane and the lysis of bacterial cell. 29 The released Cu 2+ ions were also found to interact with negatively charged components of the cell wall and membrane, leading to denaturation and alteration of the membrane proteins. 30 Copper ions inside the bacterial cell generate ROS, leading to alterations in cellular signalling and interfering with the nucleic acid, resulting in an altered helical structure.…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports have suggested that antibacterial activities of CuNPs lead to rapid DNA degradation and reduction of bacterial respiration (Concha‐Guerrero et al . 2014). Other possible antibacterial mechanism involves elution of Cu 2+ ions from nanoparticles, which easily gets absorbed on bacterial cell membrane and damages the membrane either by altering their enzyme functions or by solidifying proteins (Raffi et al .…”
Section: Resultsmentioning
confidence: 99%
“…Copper ions released from CuNPs have grater affinity towards these groups leading to alteration of membrane proteins, electron transport chain and inhibition of cytochromes of Gram-negative cell membranes (Orell et al 2010). Literature reports have suggested that antibacterial activities of CuNPs lead to rapid DNA degradation and reduction of bacterial respiration (Concha-Guerrero et al 2014). Other possible antibacterial mechanism involves elution of Cu 2+ ions from nanoparticles, which easily gets absorbed on bacterial cell membrane and damages the membrane either by altering their enzyme functions or by solidifying proteins (Raffi et al 2010;Slavin et al 2017).…”
Section: Antibacterial Activity Of Copper Nanoparticlesmentioning
confidence: 99%
“…Although the bacterial community analyses were performed for composite samples to take into account the heterogeneity, the analysis provided accurate information as previously reported for other studies (Concha‐Guerrero et al . 2015; Liu et al . 2015).…”
Section: Resultsmentioning
confidence: 99%